DOP83 Efficacy and Safety of Ustekinumab for Ulcerative Colitis Through 3 Years: UNIFI Long-term Extension. (27th May 2021) - Abreu, M T; Danese, S; Sandborn, W J; Miao, Y; Tikhonov, I; Zhang, H; Panaccione, R; Hisamatsu, T; Scherl, E J; Leong, R W; Rowbotham, D S; Arasaradnam, R P; et al.
Abstract: Background: Ustekinumab (UST) is an IL-12/23p40 antagonist used to treat pts with moderate-to-severe ulcerative colitis (UC). The ongoing UNIFI long-term extension (LTE) evaluates subcutaneous (SC) 90mg UST maintenance therapy, with efficacy (wk152) and safety (wk156) results reported here. Methods: 523 intravenous UST induction responders were randomized to SC maintenance therapy (175 SC placebo [PBO]; 172 UST 90mg every 12 weeks [q12w]; 176 UST 90mg q8w). 284 UST pts who completed wk44 entered the LTE. PBO pts were discontinued after wk44 unblinding. Starting at wk56, randomized pts with UC worsening could adjust to q8w. Symptomatic remission (Mayo stool frequency subscore of 0 or 1 and a rectal bleeding subscore of 0) was evaluated in randomized pts. Safety was evaluated for all 588 pts treated in the LTE, including the randomized and nonrandomized populations; 188 received PBO and 457 received UST. The nonrandomized population included responders to PBO induction and UST induction nonresponders at wk8 who received SC UST, responded 8 wks later and received UST 90mg q8w. Results: Among all pts randomized to UST at maintenance baseline (intent-to-treat population with nonresponder imputation for missing data and treatment failure criteria), 55.2% were in symptomatic remission at wk152 (biologic naïve, 66.1%; biologic failures, 43.5%; Table 1); 96.4% (185/192) of pts in symptomatic remission at wk152 were corticosteroid-free. Overall, 20.1% (39/149 biologic failure, 16/149 biologic naïve) of pts who were randomized to UST and treated in the LTE discontinued treatment between wks44 and 156. Among randomized pts treated with UST in the LTE, 67.6% were in symptomatic remission at wk152; 76.4% of those in clinical remission at wk44 were in symptomatic remission at wk152; and 84.1% of pts with observed data at wk152 were in symptomatic remission. From maintenance wk0-156, combined UST and PBO pts had 1281.6 and 425.0 pt-years of follow-up, respectively; and safety events per 100 pt-years of follow-up for combined UST vs PBO were AEs: 235.81 vs 204.48, SAEs: 7.73 vs 7.53, and serious infections: 2.34 vs 2.35 (Table 2). From wks96-156, there were no reported deaths or major adverse cardiovascular events. One UST-treated pt with fair skin and a prior history of basal cell carcinoma (BCC) reported 2 BCC. One 90 mg q8w UST pt receiving concomitant 6-MP reported SAEs of neutropenic sepsis and oral herpes SAE; the latter events were considered potential opportunistic infections. The dose of 6-MP was reduced, pt recovered and continued UST. Conclusion: The efficacy of UST in pts with UC was sustained through 3 years. No new safety signals were observed.